63.2k views
4 votes
The first step in determining the solution to the system of equations, y = –x^2 – 4x – 3 and y = 2x + 5, algebraically is to set the two equations equal as –x^2 – 4x – 3 = 2x + 5. What is the next step?

User Pkr
by
5.4k points

1 Answer

5 votes

Answer:

The next step is to put all terms into the left side of the equation and group the like trems

Explanation:

The first step in determining the solution to the system of equations,
y =-x^2-4x-3 and
y = 2x + 5, algebraically is to set the two equations equal as
-x^2-4x-3 = 2x + 5.

The next step is to put all terms into the left side of the equation and group the like trems:


-x^2-4x-3-2x-5=0,\\ \\-x^2+(-4x-2x)+(-3-5)=0,\\ \\-x^2-6x-8=0.

Now you can multiply this equation by -1:


x^2+6x+8=0

and solve it using quadratic formula:


x_(1,2)=(-6\pm √(6^2-4\cdot 8\cdot 1))/(2\cdot 1)=(-6\pm√(4))/(2)=(-6\pm 2)/(2)=-4,\ -2.

User Azhar Khan
by
5.5k points